Novel 2-phenyl-4H-chromen derivatives: synthesis and anti-inflammatory activity evaluation in vitro and in vivo - Yun Xiao; Yaoyao Yan; Juncheng Du; Xiaoxiao Feng; Famin Zhang; Xu Han; Yong Hu; Xinhua Liu (Journal of Enzyme Inhibition and Medicinal Chemistry)
It is significant to design, synthesise and optimise flavonoid derivatives with better anti-inflammatory activity. This study aims to design and synthesise a series of novel 2-phenyl-4H-chromen-4-one compounds with anti-inflammatory; among them, compound 8 was discovered as the best one. And then, the effects of compound 8 on the TLR4/MAPK signalling pathway was carried out in vivo, the results indicated that compound 8 could downregulate NO, IL-6, and TNF-α expression, and suppress LPS-induced inflammation by inhibiting the TLR4/MAPK pathways. Furthermore, compound 8 reduced inflammation by a mouse model of LPS-induced inflammatory disease in vivo. The results suggest that compound 8 has the potential against inflammation through regulating TLR4/MAPK pathway and can be assessed further for drug development.